A Comparison Between Different Reception Diversity Schemes of a 4G-LTE Base Station in Reverberation Chamber: A Deployment in a Live Cellular Network - Barazzetta, Massimo; Micheli, Davide; Bastianelli, Luca; Diamanti, Riccardo; Totta, Matteo; Obino, Pietro; Lattanzi, Renzo; Moglie, Franco; Primiani, Valter Mariani (IEEE transactions on electromagnetic compatibility, 2017)
The uplink performance of a real fourth-generation long-term-evolution (LTE) frequency-division multiplexing base station was observed by adopting a reverberation chamber as propagating environment. In the downlink direction, the reception of the LTE signal is limited to mobile station receivers. On the other hand, different reception schemes could be implemented by the base station in the uplink direction. Interference rejection and coordinated multipoint reception criteria are based on spatial diversity and are analyzed in a rich multipath environment. These options could be susceptible to impairments due to the presence of Gaussian noise, also including the more realistic case of a discontinuous noise source. The testing session was carried out under a collaboration program between TIM S.p.A., Nokia, and Università Politecnica delle Marche, and it ended up by introducing envisioned reception solutions of the base station in a live customer's cellular network.